Sinus rhythm endocardial mapping for channels identification in ischemic ventricular tachycardia using a modified electrophysiological triad. (19th May 2022) - Adragao, P; Nascimento Matos, D; Galvao Santos, P; Costa, FM; Rodrigues, G; Carmo, J; Salome Carvalho, M; Carmo, P; Cavaco, D; Morgado, F; Mendes, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: In a previous study it was demonstrated that an electrophysiological triad was able to identify critical isthmus in atrial flutter (AFL) patients. This triad is based in the Carto® electroanatomical mapping (EAM) version 7, which displays a histogram of the local activation times (LAT) of the tachycardia cycle length (TCL), in addition to the activation and voltage maps. Purpose: This study aimed to prospectively assess the ability of a modified electrophysiological triad to identify and localize the ventricular tachycardia's (VT) channels and entrance zones during sinus rhythm mapping. Methods: Prospective analysis of a unicentric registry of individuals who underwent ischemic VT ablation with Carto® EAM, all in sinus rhythm. All patients with non-ischemic etiology, lack of high-density EAM or lack of mapping in any of the left ventricle walls or structures were excluded. Areas of late potentials and possible channels of re-entry were compared to a modified electrophysiological triad constituted by: areas of low-voltage (<0.5mV), a site of deep histogram valley (LAT-Valley) with less than 20% density points relative to the highest density zone and a prolonged LAT-Valley duration that included 10% or more of the total activation time mapped. We also assessed the relationship between the pre-valley bar (the LAT histogram bar immediately before the prolonged LAT-Valley) and the channel entrances. Results: A total of 14 patients (14 men, median age 70 IQR 64-78 years) were included. All patients presented with ischemic VT and 86% had a previous inferior myocardial infarction. The median number of collected points were 1733 (IQR 1363─2729). All sinus rhythm maps presented with at least 1 LAT-Valley in the analysed histograms. All arrhythmias were effectively treated after undergoing radiofrequency in the LAT-Valley location, either by blocking the channel entrances or scar homogenization ablation strategy. Also, the pre-valley bar in the histogram marked all the channel entrances in the scar borders. No patient had relapse after a clinical follow up of over 6 months. Conclusion: In a prospective analysis, a modified electrophysiological triad was able to identify the scar channels in sinus rhythm in all patients. The pre-valley bar in the histogram disclosed the channel entrances. Further studies are needed to assess the usefulness of this algorithm to simplify catheter ablation and improve clinical outcomes.